Importance of site-specific analysis for steel framed buildings with passive energy dissipators - Ross, Merin; Kamatchi, P.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Recently, carrying out site-specific analyses by generation and propagation of scenario earthquake motions through soil layers is recommended in literature in addition to the seismic code provisions. On the other hand, application of passive energy dissipators is gaining importance to realize the operational performance of buildings. In the present study, the responses of a five storey steel framed building with and without viscoelastic damper and six storey steel framed building with and without tuned mass damper assumed to be situated on a rock site and three soil sites are studied for site-specific scenario earthquakes for Delhi region. Three actual soil sites are chosen and fifteen free field surface motions are obtained for two different scenario earthquakes viz., Mw = 8.5; R = 260 km from Himalayan source and Mw = 6.8; R = 25 km from Mathura source through one dimensional equivalent linear wave propagation analyses. Time history analyses are carried out and the percentage variations of displacement, acceleration and base shear responses between damped and undamped systems are studied. From the studies made, it is observed that, it is necessary to perform the site-specific analyses of buildings with passive energy dissipators considering the scenario earthquakes and actual soil conditions.